Managing Access to a Publisher Package: IEEE, IEL, and Xplore. - John C. Matylonek; Denise M. Beaubien Bennett (Issues in Science and Technology Librarianship)
The IEEE/IEE Electronic Library (IEL), using the Xplore interface, is a publisher-based service that must be managed as an aggregator service since it contains a variety of document formats (journal articles, conference proceedings, industry standards) that receive different levels of bibliographic control in library catalogs. These features require non-standard handling decisions and treatment in library catalogs and other finding aids. Many libraries are linking from catalogs to Xplore journals but not to the conference proceedings. Librarians acknowledge the value of linking from the catalog as well as the high maintenance costs involved. The expanding use of DOI links from indexes to full-text services may alleviate some of these linking concerns.